Hubungan Hipertiroid dengan Aktivitas Kerja pada Wanita Usia Subur - Sri Supadmi, Ova Emilia, Hari Kusnanto (Berita Kedokteran Masyarakat (BKM), 2007)
Background: Based on disorder mapping due to Iodine deficiency in 1998 and 2003, elimination of Iodine deficiency in household by consuming minimally 90 percent Iodine salt and giving Iodine oil capsule to fertile women in endemic Iodine deficiency, medium to severe, had been carried out. Evaluation of Iodine in urine appeared related to hyperthyroid cases, and a number of people were in critical Iodine status. Hyperthyroid especially for fertile women may cause fatigue and led to low working activity.Objective: To find out correlation between thyroid and working activity of fertile women in endemic Iodine deficiency.Method: The study was a cross-sectional design using two samples in Magelang District. The samples were 100 fertile women who were divided into two groups, namely hyperthyroid (50 persons) and norm thyroid group (50 persons) taken by using systematic sampling.Result: Bivariate analysis showed significant relationship between hyperthyroid and working activity (RP=4.10; 95%Cl; 2.32 - 7.24). Using stratification analysis it was found that hyperthyroid were higher among women with hormonal contraceptive (RP=6.45; 95%Cl; 2.55 - 16.34) and consumed Iodine capsule (RP=4.73; 95%Cl; 2.37 - 9.43).Conclusion: There was a significant correlation between hyperthyroid and working activity of fertile women. Hyperthyroid women tend to have lower working activity (four times lower) than norm thyroid women. The modified effects were hormonal contraceptive and Iodine capsule factors. The factors not affecting the correlation between hyperthyroid and working activity of fertile women were age, Body Mass Index (BMI) and Iodine salt consumption.Keywords: Iodine deficiency, hyperthyroid, working activity